Seçim kampanyalarında iktidar ve muhalefet söylemlerinin seçim sonucuna yansıması bakımından karşılaştırılması : 2019 İstanbul Büyükşehir Belediyesi yerel seçimi - Topuz, Mehmet (My University, 2023)
Siyasal seçim kampanyası aday, parti ve parti örgütünün bütüncül çalışması ile meydana gelmektedir. Seçim kampanyası döneminde iktidar ve muhalefet partileri söylemleri ile seçim sonucuna etki etmektedir. Bu noktadan hareketle tez çalışmasında 2019 İstanbul Büyükşehir Belediye yerel seçimi iktidar ve muhalefet partisinin vaat ve söylemleri karşılaştırmalı olarak incelenmiştir. Bu çalışmada 2019 İstanbul Büyükşehir Belediye seçim kampanyasında aday ve parti tarafından ortaya konan iktidar ve muhalefet söylemlerinin seçim sonucuna nasıl etti ettiği ortaya çıkarılmaya çalışılmıştır. Siyasal iletişimin halkla ilişkiler çalışma alanına giren bir disiplindir. İktidar ve muhalefet partisi söylemlerinin seçim sonucuna nasıl etki ettiği varsayımından hareketle tez çalışmasının halkla ilişkiler alanına yeni bir bakış açısı getirmesi ve rota olması beklenmektedir. Bu tez çalışmasında söylem analizi yöntemi ile 31 Mart 2019 İstanbul Büyükşehir Belediye başkanlığı yerel seçimi incelenmiştir.

COMPARISON OF THE POWER AND OPPOSITION DISCUSSIONS IN ELECTION CAMPAIGNS IN TERMS OF ITS REFLECTION ON THE ELECTION RESULT: 2019 ISTANBUL METROPOLITAN MUNICIPALITY ELECTION The political election campaign is formed by the holistic work of the candidate, the party and the party organization. During the election campaign period, the ruling and opposition parties affect the election results with their discourses. From this point of view, in the thesis study, the promises and discourses of the ruling and opposition parties in the 2019 Istanbul Metropolitan Municipality local elections were examined comparatively. In this study, it was tried to reveal how the discourses of power and opposition put forward by the candidate and the party in the 2019 Istanbul Metropolitan Municipality election campaign affected the election result. It is a discipline that falls into the public relations study area of political communication. Based on the assumption of how the discourses of the ruling and opposition parties affect the election result, it is expected that the thesis study will bring a new perspective to the field of public relations and become a route. In this thesis study, the 31 March 2019 Istanbul Metropolitan Municipality local election was examined with the method of discourse analysis.
Comparison of the power and opposition discussions in election campaigns in terms of its reflection on the election result : 2019 Istanbul Metropolitan Municipality election
Keywords: Belediye yönetimi; Communication; Election campaign; Elections; Istanbul; İktidar; İletişim; İstanbul; İstanbul Büyükşehir Belediyesi; Local election; Local government; Muhalefet; Municipal government; Opposition; Political campaigns; Political communication; Politics and government; Power; Propaganda; Seçim kampanyası; Seçimler; Siyasal iletişim; Siyasal kampanyaları; Siyaset ve yönetim; Turkey; Türkiye; Yerel seçim; Yerel yönetim